A multi-AUV cooperative hunting method in 3-D underwater environment with obstacle. (April 2016) - Huang, Zongrui; Zhu, Daqi; Sun, Bing
Abstract: A multi-AUV cooperative hunting algorithm based on bio-inspired neural network is proposed for 3-D underwater environment with obstacle. Firstly, AUV 3-D working environment is represented by biological inspired neural network model, and there is one-to-one correspondence between each neuron in neural network and the position of the grid map of underwater environment. Then the activity value of neurons is used to guide each hunting AUV navigation and obstacle avoidance. A high efficient path for each hunting AUV is arranged and finally the target is surrounded by AUVs. Lastly, to demonstrate the effectiveness of the proposed algorithm, simulation results are given in this paper.